Anteroposterior Laxity After Bicruciate-Retaining Total Knee Arthroplasty Is Closer to the Native Knee Than ACL-Resecting TKA: A Biomechanical Cadaver Study. - Halewood,C; Traynor,A; Bellemans,J; Victor,J; Amis,AA (Journal of Arthroplasty, 2015)
The purpose of this study was to examine whether a bicruciate retaining (BCR) TKA would yield anteroposterior (AP) laxity closer to the native knee than a posterior cruciate ligament retaining (CR) TKA. A BCR TKA was designed and compared to CR TKA and the native knee using cadaver specimens. AP laxity with the CR TKA was greater than the native knee (P=0.006) and BCR TKA (P=0.039), but no difference was found between the BCR TKA and the native knee. No significant differences were found in rotations between the prostheses and the native knee. BCR TKA was shown to be surgically feasible, reduced AP laxity versus CR TKA, and may improve knee stability without using conforming geometry in the implant design.